Pelatihan Digital Marketing Plan sebagai Upaya Peningkatan Penjualan Produk Usaha Mikro Kecil dan Menengah di Desa Kebalan Kulon - Wilujeng Asih Purwani; Anita Rahmah Dewi; Ahmad Laroybafih; Abdullah Syakur; Ahmad Romy Rohmatullah; Ahmad Kharis Khoiri; Eka Fitriyana; Iva Imroatus Sholihah; Yulia Chindiana; Suyetno; Wanda Hamidatuz Zahroh (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
Kebalan Kulon Village is one of the villages in Lamongan Regency, East Java. This village has quite a good potential in its role in the field of UMKM (Micro, Small, and Medium Enterprises). The UMKM products produced are food products produced by local communities. The food products produced are products that have high selling power. The product marketing process that has been carried out by the UMKM group is through consignment at supermarkets. This is a concern for researchers from Billfath University to participate in product marketing so training is needed in the form of effective marketing planning through digital systems. It is hoped that the digital sales system will provide opportunities for UMKM to make the sales process easier. Sales made digitally are expected to provide significant profits. This research method is descriptive qualitative. The training carried out by the Billfath University Community Service team was to provide technical sales guidance through the marketplace by guiding all UMKM members in Kebalankulon Village in utilizing digital sales technology.